LENGTH-WEIGHT RELATIONSHIP IN THE MALABAR SOLE, CYNOGLOSSUS MACROSTOMUS NORMAN - Victor, A C C (Indian Journal of Fisheries, 2011)
The length-weight relationship of the Malabar sole, Cynoglossus macrostomusNorman was studied. The difference between the regression coefficients of malesand females was not significant at 5% level.